Metabolic syndrome and metastatic prostate cancer correlation study, a real-world study in a prostate cancer clinical research center, Xinjiang, China - An, Hengqing; Ma, Dongsheng; Mei, Yujie; Wang, Lulu; Maimaitiyiming, Abudukeyoumu; Zhuo, Tao; Aihaiti, Renaguli; Bu, Ke; Huang, Xin; Zhang, Kaige; Yao, Miao; Ling, Chenyang; et al. (Frontiers in Endocrinology, 2022)
Objective The aim of this study was to investigate the relevance of metabolic syndrome (MetS) and metabolic scores to the occurrence, progression and prognosis of metastatic prostate cancer (mPCA),assessing the definition of the variables of metabolic syndrome, and the potential mechanisms of MetS and mPCA. Methods Data were obtained from the database of prostate cancer follow-up at the Urology Centre of the First Affiliated Hospital of Xinjiang Medical University (N=1303). After screening by inclusion and exclusion criteria, clinical data of 190 patients diagnosed with mPCA by pathology and imaging from January 2010 to August 2021 were finally included, including 111 cases in the MetS group and 79 cases in the Non-MetS group. Results The MetS group was higher than the Non-MetS group: T stage, Gleasson score, initial PSA, tumour load, PSA after 7 months of ADT (P<0.05),with a shorter time to progression to CRPC stage(P<0.05)[where the time to progression to CRPC was relatively shorter in the high metabolic score subgroup of the MetS group than in the low subgroup (P<0.05)].Median survival time was significantly shorter in the MetS group than in the Non-MetS group (P<0.05),and there was a correlation with metabolic score, with the higher metabolic score subgroup having a lower survival time than the lower metabolic score subgroup (P<0.05) Conclusion Those with mPCA combined with MetS had lower PSA remission rates, more aggressive tumours, shorter time to progression to CRPC and shorter median survival times than those with mPCA without MetS.Tumour progression and metabolic score showed a positive correlation, predicting that MetS may promote the progression of mPCA, suggesting that MetS may be a risk factor affecting the prognosis of mPCA.